3D Graphene Films Enable Simultaneously High Sensitivity and Large Stretchability for Strain Sensors. (13th August 2018) - Pan, Fei; Chen, Si‐Ming; Li, Yuhan; Tao, Zhuchen; Ye, Jianglin; Ni, Kun; Yu, Han; Xiang, Bin; Ren, Yibin; Qin, Faxiang; Yu, Shu‐Hong; Zhu, Yanwu
Abstract: Integration of 2D membranes into 3D macroscopic structures is essential to overcome the intrinsically low stretchability of graphene for the applications in flexible and wearable electronics. Herein, the synthesis of 3D graphene films (3D‐GFs) using chemical vapor deposition (CVD) is reported, in which a porous copper foil (PCF) is chosen as a template in the atmospheric‐pressure CVD preparation. When the 3D‐GF prepared at 1000 °C (noted as 3D‐GF‐1000) is transferred onto a polydimethylsiloxane (PDMS) membrane, the obtained 3D‐GF‐1000/PDMS hybrid film shows an electrical conductivity of 11.6 S cm −1 with good flexibility, indicated by small relative resistance changes (Δ R / R 0 ) of 2.67 and 0.36 under a tensile strain of 50% and a bending radius of 1.6 mm, respectively. When the CVD temperature is reduced to 900 °C (generating a sample noted as 3D‐GF‐900), the 3D‐GF‐900/PDMS hybrid film exhibits an excellent strain‐sensing performance with a workable strain range of up to 187% and simultaneously a gauge factor of up to ≈1500. The 3D‐GF‐900/PDMS also shows a remarkable durability in resistance in repeated 5000 stretching‐releasing cycles. Kinetics studies show that the response of Δ R / R 0 upon strain is related to the graphitization and conductivity of 3D‐GF which are sensitive to the CVD preparation temperature. Abstract : Integration of 2D membranes into 3D macroscopic structures is an efficient way to achieve high stretching range. Based on 3D graphene films (3D‐GFs) grown on porous Cu foils, a reversible change of resistance under large stretching or bending can be realized. The 3D‐GF‐900/polydimethylsiloxane strain sensor showed workable strain range up to 187% and gauge factor up to ≈1500.